Geographic Analysis of Agriculture in various Climatic conditions using Big Data Analytics - ANITA RAJKUMAR; Dr. S Shakila (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Big data Analytics is dealing with large and multi-dimensional information. Geographic information have been received from various source like, satellites, remote sensors, with various attributes like, date, time, soil type, location, climatic condition, water status, and etc. Using Clustering and machine learning techniques, the accuracy of the changes will be more positive. Agriculture industries would mainly want to decide the forecast as there were stories related to the loss due to the wrong predictions towards the farming of products. For an Agricultural industry, Geographical information and climatic conditions are very vital for deciding their daily activities.